2022
DOI: 10.1007/s10552-022-01647-x
|View full text |Cite
|
Sign up to set email alerts
|

Use a web-app to improve breast cancer risk factors and symptoms knowledge and adherence to healthy diet and physical activity in women without breast cancer diagnosis (Precam project)

Abstract: Purpose This study aimed to evaluate the preliminary effectiveness of an educational intervention using a web-app to improve knowledge of breast cancer risk factors and symptoms and adherence to healthy eating and physical activity among women without breast cancer diagnosis in Asturias (Spain). Methods A pragmatic randomized pilot trial was conducted to evaluate the impact of a web-app-based intervention for women without breast cancer diagnosis. Women i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 36 publications
(42 reference statements)
0
1
0
Order By: Relevance
“…The comparison of face-to-face and online psychotherapy or support groups for cancer survivors showed no significant difference, thereby suggesting the potential of online interventions to overcome geographical barriers 30,31 . Martín-Payo et al 32 demonstrated how a web-app based on Behavior Change Wheel Model improved adherence to healthy behaviors, and significantly facilitated the identification of risk factors and symptoms in the intervention group of breast cancer patients.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The comparison of face-to-face and online psychotherapy or support groups for cancer survivors showed no significant difference, thereby suggesting the potential of online interventions to overcome geographical barriers 30,31 . Martín-Payo et al 32 demonstrated how a web-app based on Behavior Change Wheel Model improved adherence to healthy behaviors, and significantly facilitated the identification of risk factors and symptoms in the intervention group of breast cancer patients.…”
Section: Resultsmentioning
confidence: 99%
“…Among the digital interventions included in this systematic review, the rate of effectiveness, intended as the capability of such solutions to reach the intended outcomes for which they have been proposed to, varies depending on the area the interventions focuses on: the digital interventions for improving psychophysical well-being proved to be the most effective, with 80% (12 out of 15) of the proposed solutions 1922,2426,28,29,32,33 having a positive impact on mental health; followed by remote monitoring interventions, with 73% (8 out of 11) of included studies 42,44,45,4853 resulting useful for patients for real-time self-reporting symptoms and vitals and assessing their quality of life; also digital interventions for managing physical side-effects of cancer treatments are quite effective with 71% (5 out of 7) of the solutions 26,34,35,37,40 helping coping with physical distress; finally, only the 17% (2 out of 12) solutions 62,64 proved to enhance empowerment and self-efficacy of cancer patients. Moreover, for the first two categories, the adherence rate is quite high, ranging from 59% to 100%, suggesting a correlation between the effectiveness and the adherence rate of such interventions whose causality could be mutual.…”
Section: Resultsmentioning
confidence: 99%
“…Yet, very limited digital health systems focus on primary prevention of breast cancer. Nonetheless, some effective interventions for young women without breast cancer diagnosis, delivered using a web-app, were found in the literature with the aim to improve the knowledge related with the tumor and to develop healthy behaviors ( Gajda et al, 2018 ; Martín-Payo et al, 2023 ).…”
Section: Introductionmentioning
confidence: 99%